Identification of the AHP family reveals their critical response to cytokinin regulation during adventitious root formation in apple rootstock - Li, Ke; Li, Huan; Liang, Wei Ling; Liu, Jing Ju; Tian, Hui Yue; Wang, Li Hu; Wei, Yan Hong (Frontiers in Plant Science, 2025)
Adventitious root (AR) formation is a bottleneck for vegetative proliferation. In this study, 13 AHP genes (MdAHPs) were identified in the apple genome. Phylogenetic analysis grouped them into 3 clusters (I, II, III), with 4, 4, and 5 genes respectively. The 13 MdAHPs family members were named MdAHP1 to MdAHP13 by chromosome positions. The physicochemical properties, phylogenetic relationship, motifs, and elements of their proteins were also analyzed. The amino acid quantity varied from 60~189 aa, isoelectric point lay between 4.10 and 8.93, and there were 3~7 protein-conserving motifs. Excluding MdAHP6, other members’ promoter sequences behaved 2-4 CTK response elements. Additionally, the expression characteristics of MdAHPs family members at key stages of AR formation and in different tissues were also examined with exogenous 6-BA and Lov treatments. The results showed that MdAHP3 might be a key member in AR formation. GUS staining indicated that the activity of the MdAHP3 promoter was also significantly enhanced by CTK treatment. The protein interactions of MdAHP3/MdAHP1 and MdAHP3/MdAHP6 were verified. Compared with WT, 35S::MdAHP3 transgenic poplars inhibited AR formation. The above experimental results suggested that MdAHP3, as a key family member, interacts with MdAHP1 and MdAHP6 proteins to jointly mediate AR formation in apple rootstocks.